Differentiation is key: should employers offer something unique or the same yet better?. Issue 5 (2nd September 2020) - Wille, Lien; Derous, Eva; Weijters, Bert
ABSTRACT: Researchers agree that employers should differentiate themselves from their competitors to become the employer of choice. However, from the recruitment literature, it is not clear how employers should differentiate their employment offers. Building upon the structural alignment theory, we investigated in two experimental studies whether offering something unique (i.e., non-alignable attributes; e.g., offer a benefit package when competitors do not) or offering the same yet better (i.e., alignable attributes; e.g., offer a bigger benefit package than competitors) is the most effective differentiation strategy for employment offers and whether this depends on job seekers' work experience. Offering the same yet better affected job seekers' preferences more positively than offering something unique in lowly complex judgement and decision-making situations (Study 1) as well as in highly complex judgement and decision-making situations if job seekers had more work experience (Study 2). Hence, our findings suggest that differentiation strategies matter: employers should differentiate by offering the same yet better, particularly when they look for highly experienced job seekers in highly complex judgement and decision-making situations.